THE PORTRAYAL OF PANDEMIC IN AMERICAN MOVIES - Rudy Rudy; Firman Arofati Zalukhu; Kevin Susanto Manurung (BASIS (Bahasa dan Sastra Inggris), 2021)
With the purpose of understanding the pandemic issue that is currently experienced by almost all countries, this library research examines American films with a pandemic theme to find out the reason for using this theme in films and to identify the symbol of pandemic shown in the films. By observing the dialogs and scenes in Outbreak (1995), I am Legend (2007), Carriers (2009), Contagion (2011), and The World War Z (2013), this textual analysis study utilizes the theory of representation to interpret the pandemic in the films. The results showed that the pandemic issue can be considered a promising theme because the concept of the theme includes interesting scenes such as the emergence of infectious disease, rapid virus transmission, high mortality rates, and challenges in overcoming pandemic. These scenes form a pattern – confusion, panic, emergency, survival, and treatment that can be the hallmark of a pandemic-themed film. In addition, the results of the study also suggested that films about pandemics can symbolize the reality of human’s life which is reflected through the portraits of greed, heroism, and hope.